2023
DOI: 10.1161/circheartfailure.122.010152
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes With Peripheral Venoarterial Extracorporeal Membrane Oxygenation for Suspected Acute Myocarditis: 10-Year Experience From the Extracorporeal Life Support Organization Registry

Abstract: Background: Acute myocarditis can result in severe hemodynamic compromise requiring venoarterial extracorporeal membrane oxygenation (VA-ECMO). Outcomes and factors associated with mortality among myocarditis patients are not well described in the modern ECMO era. Methods: We queried the Extracorporeal Life Support Organization registry from 2011 to 2020 for adults with suspected acute myocarditis undergoing peripheral VA-ECMO support. The primary outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Given this potential for rapid deterioration, a low threshold for ECMO support, even in patients with conduction abnormalities, with the goals of improving cardiac output and unloading a struggling LV is paramount. This is underscored by a recent analysis by Nunez et al 9 using the Extracorporeal Life Support Organization (ELSO) Registry which demonstrated that increased utilization of peripheral ECMO in adults with AFM and cardiogenic shock from 2011 to 2020 has paralleled a decrease in in-hospital mortality from 44% to 31%. Over the entire study period, mortality was 34.9% for patients with AFM which compared favorably to all comers supported with ECMO where mortality was significantly higher at 58.3% (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this potential for rapid deterioration, a low threshold for ECMO support, even in patients with conduction abnormalities, with the goals of improving cardiac output and unloading a struggling LV is paramount. This is underscored by a recent analysis by Nunez et al 9 using the Extracorporeal Life Support Organization (ELSO) Registry which demonstrated that increased utilization of peripheral ECMO in adults with AFM and cardiogenic shock from 2011 to 2020 has paralleled a decrease in in-hospital mortality from 44% to 31%. Over the entire study period, mortality was 34.9% for patients with AFM which compared favorably to all comers supported with ECMO where mortality was significantly higher at 58.3% (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Over the entire study period, mortality was 34.9% for patients with AFM which compared favorably to all comers supported with ECMO where mortality was significantly higher at 58.3% (p < 0.001). 9 Survival rates for children with myocarditis requiring ECMO have generally been slightly higher than adult cohorts. Although earlier analysis of the ELSO registry noted 61% survival of a cohort from 1995 to 2006, 10 more recent analyses have demonstrated survival of approximately 72% in a cohort from 2007 to 2018.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Circulation: Heart Failure, Nunez et al 8 discuss outcomes, complications, and factors associated with mortality in 850 patients with suspected FM requiring peripheral VA-ECMO initiation. Data were obtained retrospectively from the Extracorporeal Life Support Organization (ELSO) registry between 2011 and 2020.…”
Section: See Article By Nunez Et Almentioning
confidence: 99%
“…Unmodifiable and modifiable factors identified by the Extracorporeal Life Support Organization (ELSO) registry analysis and other multicenter registries on FM suggest VA-ECMO support strategies must be initiated rapidly. 5,6,8 Outcomes in these patients may be impacted by timely histological diagnosis by endomyocardial biopsy (EMB), immunomodulation, left ventricular (LV) unloading to assist with recovery, and optimal management of anticoagulation to minimize ischemic and bleeding complications.…”
Section: Immunosuppression In Patients With Fm Onmentioning
confidence: 99%
See 1 more Smart Citation